LC3-Associated Phagocytosis (LAP): A Potentially Influential Mediator of Efferocytosis-Related Tumor Progression and Aggressiveness - Asare, Patrick F.; Roscioli, Eugene; Hurtado, Plinio R.; Tran, Hai B.; Mah, Chui Yan; Hodge, Sandra (Frontiers in Oncology, 2020)
One aim of cancer therapies is to induce apoptosis of tumour cells. Efficient removal of the apoptotic cells requires coordinated efforts between the processes of efferocytosis and LC3-associated phagocytosis (LAP). However, this activity has also been shown to produce anti-inflammatory and immunosuppressive signals that can be utilised by live tumour cells to evade immune defence mechanisms, resulting in tumour progression and aggressiveness. In the absence of LAP, mice exhibit suppressed tumour growth during efferocytosis, while LAP-sufficient mice show enhanced tumour progression. Little is known about how LAP or its regulators directly affect efferocytosis, tumour growth and treatment responses, and identifying the mechanisms involved has the potential to lead to the discovery of novel approaches to target cancer cells. Also incompletely understood is the direct effect of apoptotic cancer cells on LAP. This is particularly important as induction of apoptosis by current cytotoxic cancer therapies can potentially stimulate LAP following efferocytosis. Herein, we highlight the current understanding of the role of LAP and its relationship with efferocytosis in the tumour microenvironment with a view to presenting novel therapeutic strategies.